2005
DOI: 10.1097/01.ju.0000147177.20458.73
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Laparoscopic Partial Nephrectomy in 200 Cases

Abstract: Laparoscopic partial nephrectomy is an advanced procedure with potential for complications. It requires considerable experience with reconstructive laparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
139
2
12

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(157 citation statements)
references
References 16 publications
4
139
2
12
Order By: Relevance
“…While intraoperative bleeding from the tumour resection bed is usually recognized and can be addressed by oversewing the parenchyma or the bleeding vessel, recognizing postoperative haemorrhage can be more challenging, especially when patients present days or weeks after surgery. Overall, postoperative haemorrhage after LPN has been reported to be 4.2-6% [8,9]. Delayed postoperative haemorrhage has not been well defined separately but appears to occur in 1.2% of small tumour cases and in up to 7.5% of more complex cases involving centrally located tumours [4,6,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While intraoperative bleeding from the tumour resection bed is usually recognized and can be addressed by oversewing the parenchyma or the bleeding vessel, recognizing postoperative haemorrhage can be more challenging, especially when patients present days or weeks after surgery. Overall, postoperative haemorrhage after LPN has been reported to be 4.2-6% [8,9]. Delayed postoperative haemorrhage has not been well defined separately but appears to occur in 1.2% of small tumour cases and in up to 7.5% of more complex cases involving centrally located tumours [4,6,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Review of the literature showed that delayed bleeding after LPN was most often associated with RAP. To the best of our knowledge, there are eight case reports describing a total of 11 cases as well as four case series describing an additional 22 cases of delayed haemorrhage after LPN secondary to RAP (Table 3 [ 4,8,[13][14][15][16][17][18][19][20][21][22][23]). Additionally, one series by Ramani et al .…”
Section: Gross Hematuria ≥ 7 Daysmentioning
confidence: 99%
See 1 more Smart Citation
“…FloSeal can be injected through a single laparoscopic port with a short application time and does not require a completely dry surgical field to be effective. Disadvantages of FloSeal include cost, possible allergic reactions and potential transmission of prion diseases (22). In the present study, FloSeal was used as single hemostatic agent in all the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies described an association between the depth of tumor invasion and rate of hemorrhage. Ramani et al (22) investigated complications associated with LPN and showed that 53% of 19 patients requiring transfusion due to hemorrhage had deep tumors. In this study, the FloSeal group tended toward significantly fewer hemorrhagic complications although the depth of tumor invasion was higher.…”
Section: Discussionmentioning
confidence: 99%